Multifunctional Periodontal Probes and Their Handheld Electronic System for Simultaneous Temperature, pH, and Depth Measurements. Issue 2 (1st February 2022) - Ritzert, Nicole L.; Rani, Asha; Ko, Tae-Jun; Kim, Jeffrey J.; Kim, Shin Ae
Abstract : Microscale temperature and pH sensors, contained within an area of 125 μ m × 750 μ m, were fabricated on disposable 3D printed periodontal probe tips (0.5-mm diameter) with Marquis color-coded calibration marks using microfabrication and electrochemical methods. The probe tips were inserted in a reusable, wireless handheld electronic system that records the temperature and pH of specific oral sites such as a gingival sulcus. The linear response and precision of each sensor were tested in solutions of varying temperature and pH representing the physiological range of the oral cavity. The temperature and pH sensors showed linear response from 25 °C to 60 °C (±0.1 °C) and pH 4.0 to pH 8.0 (±0.1 pH unit), respectively. A calibration function performed by the system software increased precision between probes tenfold for temperature sensors (deviation range: 0.69 °C to –0.07 °C) and twofold for pH sensors (deviation range: 0.07 to 0.04). Wireless communication along with compatible software provides portability and facilitates chairside use. Simultaneous measurement of temperature and pH along with gingival sulcus depth may detect early signs of inflammation that current methods, such as probing and radiography, may not identify, thus minimizing potential tissue damage caused by periodontal disease.